The Kobane Generation : Kurdish Diaspora Mobilising in France - Toivanen, Mari (Helsinki University Press, 2021)
A small Kurdish city located in northern Syria, Kobane, became symbolically significant when ISIS laid siege to the city between September 2014 and January 2015. This pivotal moment in the fight against ISIS threw the international spotlight on the Kurds. The Kobane Generation analyses how Kurdish diaspora communities mobilised in France after the breakout of the Syrian civil war and political unrest in Turkey and Iraq in the 2010s. Tens of thousands of people, mostly but not exclusively diaspora Kurds, demonstrated in major European capitals, expressed their solidarity with Kobane, and engaged in transnational political activism towards Kurdistan. In this book, Mari Toivanen discusses a series of critical events that led to different forms of transnational participation towards Kurdistan. The focus of this book is particularly on how diaspora mobilisations became visible among the second generation, the descendants of Kurdish migrants. The book addresses important questions, such as why second-generation members felt the need to mobilise and what kind of transnational participation this led to. How did the transnational participation and political activism of the second generation differ from that of their parents, and is such activism simply diasporic or also related to more global changes in political activism? The Kobane Generation offers important insights on the generational dynamics of political mobilisations and their significance to understanding diaspora contributions. More broadly, it sheds light on second-generation political activism beyond the diaspora context, analysing it in relation to global transformations in political subjectivities.